Extrusão dos implantes em portadores de cavidade anoftálmica - Schellini, Silvana Artioli [UNESP]; Ichida, Flavia Keiko [UNESP]; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2007)
Purpose: To evaluate the characteristics of patients with anophthalmic cavity who developed sphere extrusion. Methods: A retrospective observational study was done evaluating 37 patients with anophthalmic cavity and sphere extrusion at the Faculdade de Medicina de Botucatu-UNESP. Results: Extrusion was observed in enucleated and eviscerated cavities. The majority of the patients had the eye removed because of phthisis bulbi or trauma and the extrusion happened 1 or 2 years after the surgery. Extrusion was preceded by conjunctival dehiscence and exposure of the sphere and occurred with all used implants. Conclusion: Complications after orbital implant placement are a possibility. Dehiscence and sphere extrusion may happen and another surgery would be necessary. The patient and the ophthalmologist have to be prepared for this.
Anophthalmic cavity and implant extrusion
Keywords: Eye enucleation; Hydroxyapatites; Orbital diseases; Orbital implants/adverse effects; Sclera; Silicone elastomers; polymer; adolescent; adult; aged; child; enucleation; eye injury; eye surgery; female; foreign body; human; male; middle aged; orbit disease; orbit implant; preschool child; reoperation; retrospective study; statistics; time; wound dehiscence; Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Eye Enucleation; Eye Evisceration; Eye Injuries; Female; Foreign-Body Migration; Humans; Male; Middle Aged; Orbital Diseases; Orbital Implants; Polymers; Reoperation; Retrospective Studies; Surgical Wound Dehiscence; Time Factors